Determination of the steady-state response of viscoelastically point-supported rectangular orthotropic plates - Kocatürk, T; Altintas, G (CONSULTANTS BUREAU, 2003)
In the present study, the steady-state response to a sinusoidally varying concentrated force acting at the center of a rectangular point-supported orthotropic elastic plate is analyzed. The equation of the plate is represented by finite-difference expressions. By using the ordinary finite-difference technique, the problem is reduced to the solution of a system of algebraic equations. The influence of mechanical properties of the plate material on the vibration modes and the steady-state response of the plate is investigated numerically. Also, the effect of location of the point supports is studied. The problems considered are solved within the framework of the Kirchhoff-Love hypothesis.
Keywords: orthotropic plate; viscoelasticity; vibration; steady-state response; damping; VIBRATIONS; Mechanics; Materials Science; Polymer Science